The road to redemption the Jews of the Yemen 1900 - 1950 - Parfitt, Tudor 1944- (Brill's series in Jewish studies, 1996)
British immigration policies in Palestine, The Imam's efforts to prevent them from leaving, and British regulations in Aden often frustrated their efforts. This movement of people was to culminate in 1948-50 in what was the largest human airlift the world had ever seen - Operation Magic Carpet - when the Yemenites were taken 'on wings of eagles' to Israel